Risk Assessment of Coronavirus Disease (COVID-19) Transmission among Physicians Working at a COVID-dedicated Tertiary-care Hospital - Choudhury, Adnan Yusuf; Sarkar, Nirmal Kanti; Sobuj, Mofizur Rahman; Biswas, Sushanta; Roy, Moumita; Uddin, Jalal Mohsin; Hamid, Md Abdul (Mugda Medical College Journal, 2023)
Background and aims: In the earlier stage of pandemic, a sizeable number of physicians and other healthcare workers were infected with SARS-CoV-2. The aim of this study was to assess the factors associated with the risk of SARS-CoV-2 infection among physicians working at a COVID-dedicated tertiary care hospital, within and outside the medical workplace. Methods: This case control study was conducted among the physicians and surgeons working at different departments of Mugda Medical College and Hospital and undergone different pattern of exposure to COVID patients within the period of 20 April, 2020 and 20 July, 2020. Respondents were queried regarding job description, workplace exposures, respiratory protection, hospital policy of disease prevention, and extra-occupational activities during duty period. Chi-square test was done and odds ratios for physicians’ infection were calculated. A p-value <0.05 was considered as statistical significant. Results: Increased risk of SARS-CoV-2 infection in physicians was associated with the use of mobile phone during duty hour (OR, 15, 95% confidence interval 1.971 to 121.905, p=0.001), and breech of PPE during doffing (OR, 2.52, 95% confidence interval 0.821 to 7.76, p=0.099). Extra-occupational risk factors included contact with known COVID patient (OR, 5.735, 95% confidence interval 2.072 to 15.872, p=<0.001), and visit any gathering (OR, 1.076, 95% confidence interval 0.412 to 2.81, p=0.881). Physicians worked in roster group (50%) and round group (34.38%) were mostly infected than other facilities. Conclusion: COVID-19 transmissions to physicians was associated with exposure at workplace, breech in PPE during doffing, use of device during round/roster period, extra-occupational exposure to known COVID patients outside the hospital, and visit any gathering. Close monitoring of infection control measures in workplace and increase awareness of the risks of outdoor activities in pandemic situation, may reduce the incidence of infection among physicians. Mugda Med Coll J. 2022; 5(2): 93-97